2015
DOI: 10.1177/0333102414564892
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and chronobiology in cluster headache

Abstract: Diurnally, CH exhibits a relationship with night-time and annually with daylight hours. Patients' sleep quality is reduced compared with controls. Results suggest a complex relationship as sleep quality improves between clusters, but remains pathological.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
175
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(192 citation statements)
references
References 26 publications
16
175
0
1
Order By: Relevance
“…They include peptides, such as substance P, neuropeptide Y, bradykinin, enkephalins, and atrial and brain natriuretic peptides [34], involved in the central regulation of pain, vasomotion, stress and sleep-wake rhythms as well as in the modulation of trigeminal nociceptive signals, whose alterations are thought to be implied in CH and to lead to the principal clinical features of this disease [3, 35, 36]. Interestingly, constitutive NEP knockout mice showed enhanced response to noxious thermal and chemical stimuli as well as thermal hyperalgesia and allodynia, and mechanical allodynia after chronic constriction injury of sciatic nerve [37].…”
Section: Discussionmentioning
confidence: 99%
“…They include peptides, such as substance P, neuropeptide Y, bradykinin, enkephalins, and atrial and brain natriuretic peptides [34], involved in the central regulation of pain, vasomotion, stress and sleep-wake rhythms as well as in the modulation of trigeminal nociceptive signals, whose alterations are thought to be implied in CH and to lead to the principal clinical features of this disease [3, 35, 36]. Interestingly, constitutive NEP knockout mice showed enhanced response to noxious thermal and chemical stimuli as well as thermal hyperalgesia and allodynia, and mechanical allodynia after chronic constriction injury of sciatic nerve [37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that sleep disturbances are a risk factor for headaches, as reviewed in previous studies. [12][13][14][15][16][17] Sleep disturbances in patients with eczema have recently been found to be associated with shorter stature 21 and poor health-related quality of life [22][23][24][25][26] in children and poorer overall health, 3 increased fractures and other injuries, 27 and even cardiovascular disease 28 in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these features including yawning, fatigue, loss of appetite, and polyuria raise the potential for clear hypothalamic involvement in migraine given its role in sleep–wake states, appetite regulation, secretion of antidiuretic hormone (vasopressin), and nociceptive processing . While similar premonitory symptoms are not routinely reported in other primary headache disorders, the hypothalamus has gained significant attention due to the circadian and circannual periodicity of attacks including migraine and cluster headache . For example, several reports demonstrate a clear circadian pattern of migraine attack onset and circannual periodicity in cluster headaches that is inversely proportional to daylight length.…”
Section: The Emerging Role Of the Hypothalamus In Primary Headache DImentioning
confidence: 81%
“…While migraine therapy in particular is undergoing some seismic changes with the emergence of targeted calcitonin gene‐related peptide small molecule antagonists and monoclonal antibodies as well as neurally targeted serotonin 5‐HT 1F receptor agonists (ditans), there remains a significant unmet need to develop a greater understanding of the mechanisms of action of these and other potential therapeutic targets that may herald a way forward for future development. This is borne from a pre‐existing bias on treating the headache component of the disorder, considering that this may occur up to two to three days after the onset of the migraine attack, and given the clear circadian and circannual periodicity of migraine and cluster headache, there is potential for future therapies to target the non‐pain components of the attack with an aim of reducing attack susceptibility, progression, and ultimately preventing the headache.…”
Section: Introductionmentioning
confidence: 99%